CeSecom Un portale per l'Europa Centro-Orientale nel Medioevo - Lorenzo Pubblici (Electronica, 2010)
Cesecom was founded by bringing together a group of scholars who are experts in the study of the several regions that are between Central Europe and Caucasus, including Central Asia. Our attention is focused on the centuries before the fall of Constantinople and the discovery of America, a fundamental period in order to understand the roots of the problems and conflicts that are still tormenting this region of the world today. CeSecom was created to meet the exigencies of scholars in order to furnish a tool for research and also provide an open space for discussions, to exchange ideas and share the outcomes of one's studies. The website will be an open resource, whose aim is to improve diverse specializations, sharing and delving in them. We hope that this initiative will meet your liking and will favor communication of our scientific work.